Antibiotic lock solutions as adjunct therapy for catheter-related blood stream infections in pediatric hemodialysis patients - Blair, N.; Patil, P.; Nguyen, D.; Paudyal-Nepal, B.; Iorember, F. (Frontiers in Pediatrics, 2024)
The predominant use of intravenous catheters as primary access type in the pediatric hemodialysis population is associated with an increased risk of catheter related blood stream infections. While strict adherence to catheter placement and long-term care guidelines have helped to decrease the incidence of these infections, blood stream infections remain an infection burden in pediatric patients with long term hemodialysis catheters. The formation of biofilms on the surfaces of these catheters has been shown to be a source of microbes causing blood stream infections. One of the strategies for preventing bacterial colonization, inhibiting microbial multiplication, and suppressing the seeding of these microbes from biofilms upon maturation, has been the use of antibioticbased lock solutions in-between dialysis treatments. Although clinical guidelines for the use of antibiotic lock solutions are yet to be developed, available evidence suggests a beneficial role of antibiotic lock solutions in the management of catheter related blood stream infections. Additionally, a clear understanding of how biofilms are formed and their role in the pathogenesis of catheter related bloodstream infection will facilitate the development of solutions that can prevent biofilm formation and inhibit their multiplication, maturation and seeding into the bloodstream.